PENGARUH PENERAPAN MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN PENGUSAHA KENA PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA CANDISARI SEMARANG (Students' Journal of Accounting and Banking, 2015)
This study examines the effect of modernization of taxes administration toward compliance Taxable Enterprise at the KPP Pratama Candisari Semarang. This research was conducted at the KPP Pratama Candisari Semarang. The sampling technique used purposive sampling method. The population in this study is the taxpayer who is registered as a Taxable Enterprise. Relationship and (or) influence between variabel is described by using multiple regression analysis. The results showed that the organizational culture affect the compliance of Taxable Enterprise. Whereas the organizational structure, organizational procedures and organizational strategy do not affect the compliance of Taxable Enterprise.Keywords: Organizational Structure, Organizational Procedures, Organizational Strategy, Organizational Culture and Compliance Taxable Enterprise